Third Five Year Plan of Andaman and Nicobar Islands 1961-66 (Volume VII) Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1961)
There is an acute shortage of houses in private sector. the Low Income Group Housing Scheme was extended to this territory in 1957-58. Loans totaling Rs.4,921 lakhs were sanctioned upto the end of March, 1960. Construction of 10 houses were completed upto the end of March 1961, and another 29 houses were at different stages of construction.
Andaman and Nicobar Administration